THE IMPORTANCE OF MUSEUM PEDAGOGY IN THE INNOVATIVE EDUCATIONAL PROCESS - Niyozov Javlonbek Jakhongir o’g’li (Web of Journals Publishing, 2025)
This article analyzes innovative pedagogical approaches aimed at fostering knowledge, cultural awareness, aesthetic taste, and national and spiritual values in students through the effective use of museum resources in the educational process. It also highlights the educational and aesthetic potential of museum environments, their role in the modern education system, and their importance in broadening students' worldviews.